2007
DOI: 10.1352/0895-8017(2007)112[0319:agfiht]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A Good Friend is Hard to Find: Friendship Among Adolescents With Disabilities

Abstract: We asked 27 Euro American teens ages 16 to 17 with developmental disabilities in Los Angeles to describe friendships. Eleven characteristics of friendship reported in the research literature (similarity, proximity, transcending context, companionship, reciprocity, mutuality, intimacy, support, trust/loyalty, conflict management, and stability) were mentioned by at least some teens. However, most teens focused on companionship, doing activities across contexts, similarity in interests/personality, sheer proximi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
80
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 17 publications
9
80
0
Order By: Relevance
“…Second, the participants' definitions of friendship for secondary students with significant intellectual and developmental disability focused on the components of friendship that are central to children's friendships, specifically proximity, transcending context, and companionship, rather than a broader range of characteristics, such as mutuality and intimacy, typical in friendships of adolescents and adults without disabilities (Bukowski et al, 1996;Matheson et al, 2007). This contrasts previous findings which indicated that parents may consider relationships between students with and without ASD to be friendship when mutuality and intimacy are present (Kuo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Second, the participants' definitions of friendship for secondary students with significant intellectual and developmental disability focused on the components of friendship that are central to children's friendships, specifically proximity, transcending context, and companionship, rather than a broader range of characteristics, such as mutuality and intimacy, typical in friendships of adolescents and adults without disabilities (Bukowski et al, 1996;Matheson et al, 2007). This contrasts previous findings which indicated that parents may consider relationships between students with and without ASD to be friendship when mutuality and intimacy are present (Kuo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…We used the 11 components identified by Matheson et al (2007): proximity, similarity, transcending context (enacted in multiple environments), companionship, reciprocity (give-and-take relationship), mutuality (chosen by both individuals), help/support, conflict management, stability, trust/loyalty, and intimacy/disclosure. All definitions were independently coded by the first author and a trained graduate student, discussed until agreement, presented to the research team, and discussed with the peer debriefer (second author).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations